2001
DOI: 10.1055/s-2001-16529
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Gastrointestinal Bleeding due to a Jejunal Lesion of Henoch-Schönlein Purpura

Abstract: The case of a 56-year-old patient with Henoch-Schönlein purpura (HSP) and fulminant gastrointestinal bleeding is reported. The patient was admitted to hospital because of palpable purpura on both legs, painful joints and diffuse abdominal pain. Suspected HSP was histologically proven and treated with prednisolone. Despite recovery, acute gastrointestinal bleeding, with melena and a drop in hemoglobin concentration from 11.2 to 4.2 g/dl, occurred 30 days after medication was started. Immediate endoscopic examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 2 publications
1
21
1
Order By: Relevance
“…In this regard, the various gastrointestinal manifestations confirmed in our patient may not be surprising. Indeed, it has been reported that gastrointestinal bleeding may occasionally become severe enough to require transfusion or laparotomy in patients with HSP [3,[11][12][13]. However, the clinical impact of the current report should be emphasized in that this case illustrates the potential for lethal bowel bleeding, which has been mentioned in only a few previous literature [13,[17][18][19].…”
Section: Discussioncontrasting
confidence: 38%
See 3 more Smart Citations
“…In this regard, the various gastrointestinal manifestations confirmed in our patient may not be surprising. Indeed, it has been reported that gastrointestinal bleeding may occasionally become severe enough to require transfusion or laparotomy in patients with HSP [3,[11][12][13]. However, the clinical impact of the current report should be emphasized in that this case illustrates the potential for lethal bowel bleeding, which has been mentioned in only a few previous literature [13,[17][18][19].…”
Section: Discussioncontrasting
confidence: 38%
“…Otherwise, there may have been a potential discrepancy in the clinical benefit of the therapeutic regimens applied in the current patient with respect to the gastrointestinal and glomerular injuries associated with HSP. Similarly, the deterioration of gastrointestinal symptoms despite improvements in skin, joint and renal manifestations during treatment with prednisolone has been reported [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serious bleeding, requiring transfusion or surgery or leading to death, was shown in 11% of the patients, in a retrospective review of 250 French adult patients (6). The small intestine is predominantly the most involved part of the gastrointestinal tract, and the second portion of the duodenum, stomach, terminal ileum and colon are also frequently affected (9)(10)(11)(12). The endoscopic findings in gastrointestinal lesions are expressed by redness, ulcers, edema and erosions.…”
Section: B B Amentioning
confidence: 99%